FREQUENTLY ASKED QUESTIONS (FAQ) BY THE STUDENTS IN EFL CLASSROOM FKIP UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Prini Desima Evawani Ambarita; Syalaisha Syafira Irwansyah; Bertaria Sohnata Hutauruk (Dharmas Education Journal (DE_Journal), 2026)
This research aimed to find out the types of questions employed by the EFL students during teaching and learning process in the classroom; to find out the teacher’s purposes of applying those types of questions by using Telegram and Whatts Up application as the framework. This research is conducted among the EFL students at FKIP Universitas HKBP Nommensen Pematangsiantar. The necessary data was collected through direct and indirect observation between an EFL students. Based on the analysis, it appeared that the online EFL classroom interaction was dominated by the teacher. One of the causes was the passiveness of the students due to the technological glitches. The pattern and characteristics of the interaction also changed. One of the most notable changes was the difficulty to observe and manage the interaction between students. These observed features of the EFL online classroom portrayed how the class is conducted as well as ideas for other EFL teachers and practitioners to prepare and organize it. The COVID-19 pandemic has transformed the form of interaction in the EFL classroom in Indonesia. Consequently, it is vital for Indonesian EFL teachers to analyse the current form of interaction in online settings to ensure quality teaching and learning.